(untitled) (Ozone Therapy Global Journal, 2012)
With this publication, AEPROMO has already launched four issues of the "Spanish Journal of Ozone Therapy" (“Revista Española de Ozonoterapia”). Being the number Zero issued in 2010, the number One in 2011, the number Two the special supplement "Book of Abstracts of the Second International Congress IMEOF and AMOZON III International Congress” and now the number Three in 2012. An special supplement containing the "Book of Abstracts of the 3rd. Third International Congress of AEPROMO - The ozone therapy in the medical agenda" will be the number Four AEPROMO is proud to launch this issue for different reasons. The most important of all is that we have been able to overcome past issues concerning the number of papers, and the diversity of its contents. As the "Spanish Journal of Ozone Therapy" is indexed in LATINDEX (http://www.latindex.org) and DIALNET (http://www.dialnet.unirioja.es), all papers have necessarily been written as per the strict international requirements and were submitted to the "Drafting, Editorial and Evaluation Committees” of the journal for peer review.